Polska Norymberga: siedem procesów przed Najwyższym Trybunałem Narodowym, 1946–1948 - Alexander V. Prusin (Zagłada Żydów)
The Polish Supreme National Tribunal (NTN) was established in January 1946 for the purpose of bringing major Nazi perpetrators to justice. Between 1946 and 1948, the NTN heard the cases of forty-nine defendants charged with war crimes and crimes against humanity. In sharp contrast to the numerous political trials carried out in the country during the same period, in which thousands of individuals accused of “hampering socialist reconstruction” were sentenced to death or long prison terms, the NTN’s proceedings applied conventional legal and moral standards comparable to those used in Western courts and investigated each case comprehensively on its own merits.